2021
DOI: 10.1177/0300060521994926
|View full text |Cite
|
Sign up to set email alerts
|

Role of circulating tumor cells in diagnosis of lung cancer: a systematic review and meta-analysis

Abstract: Objective We systematically reviewed the literature relating to the diagnostic accuracy of circulating tumor cells (CTCs) for the clinical determination of lung cancer. Methods This meta-analysis aimed to evaluate the diagnostic accuracy of CTCs for the clinical determination of lung cancer. The PubMed, Embase, Cochrane Library, and Web of Science databases were searched for relevant studies up to 31 May 2020. The numbers of patients with true positive, false positive, false negative, and true negative results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The pooled sensitivity and specificity were 0.72 (95% CI: 0.65–0.79) and 0.96 (95% CI: 0.91–0.98), respectively, and the pooled positive and negative likelihood ratios were 16.86 (95% CI: 7.65–37.12) and 0.29 (95% CI: 0.23–0.37), respectively. Zhao and colleagues concluded that CTCs had good diagnostic value for detecting lung cancer ( 190 ).…”
Section: Future Perspectivementioning
confidence: 99%
“…The pooled sensitivity and specificity were 0.72 (95% CI: 0.65–0.79) and 0.96 (95% CI: 0.91–0.98), respectively, and the pooled positive and negative likelihood ratios were 16.86 (95% CI: 7.65–37.12) and 0.29 (95% CI: 0.23–0.37), respectively. Zhao and colleagues concluded that CTCs had good diagnostic value for detecting lung cancer ( 190 ).…”
Section: Future Perspectivementioning
confidence: 99%
“…The frequency of cervical lymph node involvement in patients with LC ranges from 1.5% to 32% 11 . LC represents the first cause of death for cancer in men and the third in women 12 . Despite advances in diagnosis and treatment, 5‐year survival is 15% 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The preliminary results indicated that when both CNHC-malignant and CNHC-uncertain were considered positive results, the sensitivity and specificity of CTCs as a biomarker for lung cancer detection were 26.3% (95% CI 11.8-48.8) and 96.2% (95% CI 94.4-97.5) at baseline 113 . Furthermore, a meta-analysis of 21 studies with 3,997 participants has assessed the overall diagnostic accuracy and reported a pooled sensitivity and specificity of 0.72 (95% CI 0.65-0.79) and 0.96 (95% CI 0.91-0.98), thus indicating that CTCs also perform well in the diagnosis of lung cancer 114 .…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%